Effects of strategic orientation and environmental change on senior management reward systems - Rajagopalan, Nandini; Finkelstein, Sydney (Strategic Management Journal, 1992)
This paper examines the effects of strategic orientation and environmental change on senior management reward systems. We develop a framework that relates differences in strategic orientations and environmental conditions to four factors–availability of multiple options, programability of behavior, cause–effect ambiguity and outcome uncertainty. Hypotheses based on this framework are tested in a sample of 50 electric utility firms across two time periods covering a total of 10 years. Consistent with theory, we find that firms with more discretionary strategic orientations offer greater compensation, more outcome-based compensation plans and greater proportion of outcome-based cash compensation than firms with less discretionary strategic orientations. Similarly, high discretion environmental periods are associated with greater pay, more outcome-based compensation plans and greater proportion of outcome-based cash compensation than low discretion environmental periods.